Fine tuning of vitamin D receptor (VDR) activity by post-transcriptional and post-translational modifications - Zenata, Ondrej; Vrzal, Radim (Oncotarget, 2017)
Vitamin D receptor (VDR) is a member of the nuclear receptor (NR) superfamily of ligand-activated transcription factors. Activated VDR is responsible for maintaining calcium and phosphate homeostasis, and is required for proper cellular growth, cell differentiation and apoptosis. The expression of both phases I and II drug-metabolizing enzymes is also regulated by VDR, therefore it is clinically important.Post-translational modifications of NRs have been known as an important mechanism modulating the activity of NRs and their ability to drive the expression of target genes. The aim of this mini review is to summarize the current knowledge about post-transcriptional and post-translational modifications of VDR.
Keywords: fosforylace; Gene Expression Regulation; mikro RNA; Transcription, Genetic; receptory kalcitriolu; genetická transkripce; Receptors, Calcitriol; Phosphorylation; MicroRNAs; Sumoylation; sumoylace; lidé; Ubiquitination; Protein Processing, Post-Translational; Humans; ubikvitinace; regulace genové exprese; posttranslační úpravy proteinů